Lessons learnt from unusual ground settlement during Double-O-Tube tunnelling in soft ground. (June 2015) - Ye, Guan-lin; Hashimoto, Tadashi; Shen, Shui-long; Zhu, He-hua; Bai, Ting-hui
Graphical abstract: Highlights: In-situ monitoring were carried out to investigate a large settlement up to 0.8 m. Cement accumulation on skin plate due to improper backfill grouting was the reason. Sophisticated management system of construction and maintenance is necessary. Abstract: The DOT (Double-O-Tube) tunnelling method has been adopted in the construction of various types of tunnels in soft ground both in Japan and in China. Recently, an unexpected ground surface settlement of approximately 0.8 m was observed in a DOT construction site in Shanghai, China. The backfill grouting injection rate had to be increased by up to 500% to control the settlement. In order to find out the reasons for the large settlement, and to reduce it to an acceptable level, in-situ monitoring, including surface settlement and subsurface settlement, was undertaken to obtain the change in ground deformation during DOT machine driving. It was found that the conventional settlement control methods, such as adjusting the earth pressure balance on the cutter face, and simultaneous backfill grouting at a normally acceptable injection rate, could not reduce the large settlement. It was also noticed that the settlement started as the DOT machine was passing, as well as after the tail had passed through. Subsequent field investigations found cement accumulation attaching to the skin plate. This was due to improper backfill grouting at the early construction stage, and the concave shape of the DOT machine. The mechanism for large settlements due to improper immediate backfill grouting was analysed. After taking countermeasures, the ground settlement was reduced to approximately 0.02 m.